Pengaruh Kemudahan Pengguna dan Manfaat Terhadap Kepuasan Pelanggan Mobile Banking BRI (BRImo) Pada Mahasiswa Universitas Lambung Mangkurat Banjarmasin - arta dina; M Hasanur Arifin; Irwansyah; Siti Rusidah (Smart Business Journal (SBJ), 2026)
This study aims to examine the effect of perceived ease of use and perceived usefulness, both partially and simultaneously, on customer satisfaction of the BRI mobile banking (BRImo) application among students of Universitas Lambung Mangkurat. The research employs a quantitative approach. The sample consists of 100 respondents selected using incidental sampling technique. Data were collected through questionnaires, and the analysis method used is multiple linear regression. The results show that perceived ease of use has a positive and significant partial effect on customer satisfaction. In addition, perceived usefulness also has a positive and significant partial effect on customer satisfaction. Simultaneously, perceived ease of use and perceived usefulness have a significant effect on customer satisfaction of the BRI mobile banking (BRImo) application among students of Universitas Lambung Mangkurat.